Effects of chromium on oxygen consumption and ammonium excretion in freshwater tilapia (Oreochromis niloticus) - Oliva-Hernández, Bessie Evelyn (2024)
Chromium VI contamination in bodies of water has occurred due to the discharge of industrial wastewater, which may come from the tanning, mining, or electroplating industry, causing serious problems for aquatic fauna, mainly fish, which may suffer histopathological alterations in gills, kidneys and intestines. This study aimed to evaluate the effect of different chromium concentrations (0.0 (control), 1.0, 5.0, 10.0, 15.0 and 30.0 mg/L) on oxygen consumption and ammonium excretion in freshwater tilapia (Oreochromis niloticus), since this species has a nutritional and economic interest in different communities of the country. This study was carried out using 42 juvenile tilapia fish weighing between 1 and 3 grams, which were placed in six tanks with different chromium concentrations. After 4 hours of exposure, they were transferred to a system with recirculating water and individual respirometers. For each concentration, a battery of 7 fish was used, to which the oxygen consumption and ammonia excretion of each respirometer were determined. The results showed that by increasing the concentration of chromium in the water (p < 0.05), oxygen consumption decreased up to 62.8% from 0.4168 mL/g/L in the control group to 0.1550 mL/g/h in the concentration of 30.0 mg/L of chromium (VI). The ammonium excretion showed the highest concentration (p < 0.05), after the fish were exósed to having been exposed to a concentration of 1 mg/L of Cr6+.